Exposure to electronic gadgets and its impact on developmental milestones among preschool children - V., Roopadevi; B. S., Shravanti; Karinagannanavar, Aravind (International Journal Of Community Medicine And Public Health, 2020)
Background: The wellbeing of the children including their physical, mental, psychological growth and development and their opportunity to achieve full potential as adults is very important. But there are several factors which affect the normal development of the children. TV, mobiles, video gaming, DVD’s and other forms of electronic gadgets have become pastimes among preschool children. Thus, this study is planned to know the exposure of electronic gadgets and its impact on the developmental milestones among preschool children. Methods: A cross sectional study was conducted at Gadag among 240 preschool children of age 2-5 years attending School. The data was collected from April 2018 to October 2018. Information was gathered from parents and teachers by using pretested semi-structured questionnaire. Frequencies, percentages and chi-square test were used in analysis. Results: In this study children using most common electronic gadgets were mobile and television for less than one hour followed by 1-2 hours usage. On an average each family had 5 members possessing 6 electronic gadgets and 3 mobiles. Majority of the children started using electronic gadget for the first time at 13-24 months. Authors found that there was significant association between electronic gadget usage and personal and social development. Conclusions: The most commonly used electronic gadgets were mobiles and television and, in this study, there is an association between total duration of electronic gadget usage and personal and social development.